2020
DOI: 10.1111/1755-6724.14304
|View full text |Cite
|
Sign up to set email alerts
|

Radial Permeability Measurements for Shale Using Variable Pressure Gradients

Abstract: Shale gas is becoming an important component of the global energy supply, with permeability a critical controlling factor for long‐term gas production. Obvious deviation may exist between helium permeability determined using small pressure gradient (SPG) methods and methane permeability obtained under actual field production with variable pressure gradients (VPG). In order to more accurately evaluate the matrix permeability of shale, a VPG method using real gas (rather than He) is established to render permeab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…However, shale reservoirs have their own particularities. The porosity and permeability of shale are much lower than those of conventional reservoirs . The pore structure is complicated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, shale reservoirs have their own particularities. The porosity and permeability of shale are much lower than those of conventional reservoirs . The pore structure is complicated.…”
Section: Introductionmentioning
confidence: 99%
“…The porosity and permeability of shale are much lower than those of conventional reservoirs. 17 The pore structure is complicated. The specific surface area is large, and the gas flow in shale is complicated.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 A shale reservoir has low porosity and poor permeability. 3 It is necessary to perform reservoir stimulation to develop a shale reservoir, and hydraulic fracturing is a mature technology. 4,5 However, the injected fluid can easily cause clay expansion, resulting in reservoir damage.…”
Section: Introductionmentioning
confidence: 99%
“…A shale reservoir has low porosity and poor permeability . It is necessary to perform reservoir stimulation to develop a shale reservoir, and hydraulic fracturing is a mature technology. , However, the injected fluid can easily cause clay expansion, resulting in reservoir damage. , In addition, huge water consumption during hydraulic fracturing is undoubtedly a serious challenge for water shortage areas .…”
Section: Introductionmentioning
confidence: 99%
“…Since the 21st century, unconventional reservoir has become one of the most important fields of oil and gas exploration and development (Montgomery and Smith, 2010;Barati and Liang, 2014;Zhang et al, 2015a). A large amount of practical experience has shown that "hydraulic fracturing is an irreplaceable technology for the exploitation of unconventional oil and gas reservoirs", and it is also a key technology for economic and effective exploitation (Clark, 1949;Almuntasheri, 2014a;Fan et al, 2020). This is because hydraulic fracturing can provide a large number of fractures in the reservoir to serve as high-speed oil and gas seepage channels.…”
Section: Introductionmentioning
confidence: 99%